Sex Scene : Media and the Sexual Revolution - Schaefer, Eric, 1959- (Book collections on Project MUSE., 2014)
Sex Scene suggests that what we have come to understand as the sexual revolution of the late 1960s and early 1970s was actually a media revolution. In lively essays, the contributors examine a range of mass media-film and television, recorded sound, and publishing-that provide evidence of the circulation of sex in the public sphere, from the mainstream to the fringe. They discuss art films such as I Am Curious (Yellow), mainstream movies including Midnight Cowboy, and sexploitation films such as Mantis in Lace; the emergence of erotic film festivals and of gay.